2011
DOI: 10.1037/a0022600
|View full text |Cite
|
Sign up to set email alerts
|

Social justifications for moral emotions: When reasons for disgust are less elaborated than for anger.

Abstract: In the present research, we tested the unreasoning disgust hypothesis: moral disgust, in particular in response to a violation of a bodily norm, is less likely than moral anger to be justified with cognitively elaborated reasons. In Experiment 1, participants were asked to explain why they felt anger and disgust toward pedophiles. Participants were more likely to invoke elaborated reasons, versus merely evaluative responses, when explaining their anger, versus disgust. Experiment 2 used a between-participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 44 publications
4
44
0
Order By: Relevance
“…Conversely, anger should be less focused on victims, or individuals who have been wronged, who generally evoke sympathy from third parties (see Goetz, Keltner, & Simon-Thomas, 2010), and when there is mutual consent between individuals, the event should be less aggravating to third parties, since no injustice has occurred. This would be consistent with other research showing that anger is a flexible emotion, sensitive to the actors' reasons for acting and the circumstances surrounding an act of wrongdoing (Piazza, Russell, & Sousa, 2013;Russell & Giner-Sorolla, 2011a, 2011b, 2011c.…”
Section: Consenting To Counter-normative Sexual Acts: Differential Efsupporting
confidence: 91%
See 3 more Smart Citations
“…Conversely, anger should be less focused on victims, or individuals who have been wronged, who generally evoke sympathy from third parties (see Goetz, Keltner, & Simon-Thomas, 2010), and when there is mutual consent between individuals, the event should be less aggravating to third parties, since no injustice has occurred. This would be consistent with other research showing that anger is a flexible emotion, sensitive to the actors' reasons for acting and the circumstances surrounding an act of wrongdoing (Piazza, Russell, & Sousa, 2013;Russell & Giner-Sorolla, 2011a, 2011b, 2011c.…”
Section: Consenting To Counter-normative Sexual Acts: Differential Efsupporting
confidence: 91%
“…We deliberately avoided the word "disgust", as research has shown that its linguistic meaning is closer to "anger" in situations theoretically more relevant to anger (e.g., unfairness; see Nabi, 2002;. Instead, we selected linguistic elements connoting the underlying physiology of disgust, pertaining to nausea and oral inhibition -terms which have been found to help dissociate disgust from anger in the past (see Horberg et al, 2009;Nabi, 2002;Piazza et al, 2013;Russell & Giner-Sorolla, 2011a, 2011b. Participants were also given a photo of an actor displaying a prototypical anger face, and a prototypical disgust face, taken from the University of California, Davis, Set of Emotion Expressions (Tracy, Robins, & Schriber, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, it has been suggested that disgust may be a less flexible emotion than other emotions, such as anger. For example, recent research indicates that anger, but not disgust, is responsive to the circumstances surrounding a transgression [21] and to intentionality [22], and that disgust is less likely than anger to be justified by cognitively elaborated reasoning [23]. The inflexibility of disgust makes sense from an evolutionary perspective because it is better to make false alarms than to risk coming into contact with a disease agent [24].…”
Section: Discussionmentioning
confidence: 99%